(untitled) (Docentes 2.0 Journal, 2023)
This essay’s main objective is to analyze technostress’s impact on Peruvian university professors’ job performance in the post-pandemic scenario, considering the integration of ICT as a relevant factor in this issue. It has methodological support in the deductive method, positivist paradigm, qualitative approach, descriptive type, and topical narrative design. A thorough review of the scientific literature will be conducted, exploring the phenomenon of technostress and its implications on the psychological well-being of university teachers. Factors contributing to technostress, such as information overload, constant interruptions, insufficient technological competence, technological dependence, and technical difficulties, will be identified. Considering the impact of technostress on the psychological well-being of university teachers, it is essential to promote self-care and emotional well-being strategies in the educational environment. This involves raising awareness about the limits of technology use, establishing regular breaks during the workday, promoting digital disconnection outside working hours, and providing psychological support and stress management training. As a final argument, knowing the impact of technostress on the psychological well-being of university teachers, it is essential to promote self-care and emotional well-being strategies, develop digital skills, and implement strategies to manage technostress. This way, it will be possible to ensure quality education, create a conducive environment for student learning, and guarantee the well-being of teachers in the post-pandemic context.